Synergy between the Faculty of Da'wah and Communication, Unisnu Jepara and the Management of the Special Branch of Fatayat NU Malaysia in Empowering the Da'wah of Aswaja An-Nahdliyyah - Wahab, Abdul; Muslimin, Khoirul; Haqqi, Muhammad Nashrul; Fajrie, Mahfudlah; Murniati, Murniati; Oktafian, Ananda Wahyu; Suroso, Suroso; Inah, Inah (Journal of Dedicators Community, 2024)
This community service was carried out between the Faculty of Da'wah and Communication, Unisnu Jepara and PCI Fatayat NU Malaysia. There are three aspects to the problem of this service: 1) The world's need for Da'wah in the style of Ahlis Sunnah wal Jama'ah; 2) The need for empowering resources and human resources related to materials, strategies, media, recognition and opportunities for preaching in the style of Ahlis Sunnah wal Jama'ah; 3) Empowering skills, initiation, innovation, collaboration opportunities, communication and problem solving formulations for Islamic da'wah problems that occur in parts of the world, so that Ahlis Sunnah wal Jama'ah style da'wah can become a universal movement. Through community service, the solutions offered are 1) Forming a "Universal Movement" for preaching in the style of Ahlis Sunnah wal Jama'ah an-Nahdliyyah; 2) Discussing and setting common goals, providing information, discussion materials, supporting self-development, formulating recognition and opportunities for universal movement; 4) Building the power of exploration, innovation and joint initiation; 5) Strengthen collaboration opportunities between Fadakom Unisnu Jepara and PCI Fatayat NU Malaysia; 6) Carry out synergy in developing da'i/da'iyah skills in various parts of the world.